Kembalinya Realisme Seni Kontemporer Sebagai Penyebab Kemunculan Seni Rupa Realisme di Setiap Zaman - Susilowati, Anna (Visualita Jurnal Online Desain Komunikasi Visual, 2020)
Many attacks on Realist Paintings, with emergence of photographic techniques, and the emergence of non-objective art that has a Cold War background between America and Russia. Many artists and critics feel that Realism is no longer sufficient to represent a new spirit after World War II. Disillusionment with war and rationality also made Adorno reject the beautiful and pleasing art of Realism style. Artists who emerged victorious in the 1950s who rejected past creeds of art, such as 'art for the people' or 'art for social reform', instead they opted for personal expression and social alienation. Such trends occur in the world of philosophy, that the theory of correspondence truth based on conformity to reality, has been abandoned. The philosophers replaced it with the Philosophy of Language. But in every period, art style realism always reappears in new forms, such as Pop Art, Photo Realism, Superrealism and Hyperrealism. This article wants to illustrate how realism is rejected and in what way realism always reappears along with its causes and also in the final section will review development of Hyperrealism in Indonesia.